TRANSFORMATION OF VANILLIN INTO OCTAHYDROXANTHENE DERIVATIVE USING GUANIDINE CATALYST - Abdussalam, Moch; Yuda, Indah Permata; Juniarti, Juniarti (Walisongo Journal of Chemistry, 2020)
Octahydroxanthene Compounds are bioactive substance which can be produced from benzaldehyde derivative. In this research, we have carried out transformation of vanilin from Indonesian natural product to octahydroxanthene derivatives compound at optimized reaction time and guanidine was used as a catalyst. Several spectroscopy methods such as IR, 1H-NMR and GC-MS were used to confirm the structure of product. The percent yield from optimation product obtained was 91% with 96% of peak area.